Students' and instructors' perceptions of powerPoint use in ELT classrooms - Ali, Hiba (Eastern Mediterranean University EMU, 2017)
The current study aimed to identify both the students’ ( graduate and undergraduate ) and the instructors’ perceptions of PowerPoint Presentation (PPP) use in ELT Classrooms. The study was conducted in the Department of Foreign Language Education ( FLE) at Eastern Mediterranean University (EMU). It also attempted to find out the differences in perceptions between the graduate and the undergraduate students as well as between the students and the instructors. This case study used mixed method approach to research. The participants of the study were 108 students ( graduate and undergraduate ) and 10 instructors of FLE Department at EMU. The data were collected using student and instructor questionnaires and interviews. The results showed that both the students and the instructors had positive perceptions regarding the use of PPP in ELT classes. They believed that PPP is an easy and interesting tool to use in the classrooms. However, they varied in their preferences concerning PPP. The data showed that the students preferred decorative and light colored backgrounds while the instructors had some uncertainties regarding these preferences. In addition, although the undergraduate and graduate students showed similarities in their perceptions regarding PPP use, they differed in their preferences. For instance, the graduate students believed that the slides should work as discussion points in the classrooms while the undergraduate students believed that slides should include interesting multimedia features. The findings of this study may have some practical implications for instructors and students. More specifically, they may help the instructors and the students to gain awareness about the important role of PPP in learning and teaching. Also, the findings may provide feedback for the instructors as regards their students’ preferences, so that they can integrate more effective PPPs into their classrooms. Moreover, the study has some suggestions for future studies such as focusing on the topics of motivation and learning styles in relation to PPP. Keywords: PowerPoint Presentation (PPP), PPP in ELT, Perceptions, Preferences.

ÖZ: Bu çalışma, hem öğrencilerin (lisans ve lisansüstü) hem de öğretim elemanlarının İngiliz Dili Öğretimi (İDÖ) sınıflarında Powerpoint Sunumları kullanımı hakkındaki görüşlerini belirlemeyi amaçlamıştır. Çalışma, Doğu Akdeniz Üniversitesi Yabancı Diller Eğitimi Bölümü’nde yürütülmüştür. Ayrıca, bu çalışma öğrenciler (lisans ve lisansüstü) ve öğretim elemanları arasındaki görüş farklılıklarını da belirlemeye çalışmıştır. Bu durum çalışmasında, araştırma yöntemi olarak karma yöntem kullanılmıştır. Çalışmanın katılımcıları Doğu Akdeniz Üniversitesi Yabancı Diller Eğitimi Bölümü’nden 108 öğrenci (lisans ve lisansüstü) ve 10 öğretim elemanıdır. Veriler, öğrenci ve öğretim elemanı anketleri ve yarı yapılandırılmış mülakatlar kullanılarak elde edilmiştir. Sonuçlar, hem öğrencilerin (lisans ve lisansüstü) hem de öğretim elemanlarının İDÖ sınıflarında kullanılan Powerpoint Sunumları hakkında olumlu algılarının olduğunu göstermiştir. Katılımcılar Powerpoint Sunumlarının kolay ve ilgi çekici araçlar olduğunu düşünmektedirler. Ancak, Powerpoint Sunumları ile ilgili tercihleri konusunda katılımcılar farklılıklar göstermektedirler. Verilere göre, öğrenciler dekoratif ve açık renkli sunumların kullanılmasını tercih ederlerken, öğretim elemanları öğrencilerin tercihleri konusunda bazı belirsizlikleri bulunmaktadır. Ayrıca, lisans ve lisansüstü öğrencileri Powerpoint Sunumları kullanımı hakkındaki algıları açısından benzerlikler gösterseler de, konuyla ilgili tercihlerinde farklılıklarının olduğu görülmüştür. Örneğin, lisansüstü öğrencileri sunumların genel olarak tartışma noktalarını içermesi gerektiğine inanırken, lisans öğrencileri sunumların çeşitli görsel ve işitsel unsurları içermesi gerektiğini düşünmektedirler. Bu çalışma sonuçlarının öğrenciler ve öğretim elemanları için bazı pratik sezdirimleri olabilir. Çalışma sonuçları, hem öğrencilerin hem de öğretim elemanlarının Powerpoint Sunumları kullanımının öğrenme ve öğretmedeki önemi konusundaki farkındalıklarını artırabilir. Ayrıca, çalışmanın bulguları öğretim elemanlarına, öğrencilerinin tercihleri hakkında geribildirim verebilir ve böylece daha etkili Powerpoint Sunumları hazırlamalarını dağlayabilir. Dahası, bu çalışma, motivasyon ve öğrenme stilleri ile Powerpoint Sunumları arasındaki ilişkiyi irdeleyecek gelecekteki çalışmalara da bazı öneriler sunabilir. Anahtar kelimeler: PowerPoint Sunumu (PPS), İngiliz Dili Öğretiminde PPS, Algılar, Tercihler.
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2017. Supervisor: Assist. Prof. Dr. Fatoş Erozan.
Keywords: English Language Teaching (ELT); English Language Teacher-Study and Teaching-Eastern Mediterranean University-Cyprus; North